Spatial proximity to wildfires as a proxy for measuring PM2.5: A novel method for estimating exposures in rural settings - M. Luke Smith; Guangqing Chi (The Journal of Climate Change and Health, 2023)
Background: : Climate change impacts humans and society both directly and indirectly. Alaska, for example, is warming twice as fast as the global mean, and researchers are starting to grapple with the varied and interconnected ways in which climate change affects the people there. With the number of wildfires increasing in Alaska as a result of climate change, the number of asthma cases has increased, driven by exposure to small particulate matter. However, it is not clear how far away smoke from wildfires can affect health. In this study, we hope to establish a relationship between proximity to wildfires and asthma in locations where direct PM2.5 measurement is not easily accomplished. Methods: : In this study, we examined whether proximity to wildfire exposure is associated with regional counts of adults with asthma, calculated using Behavioral Risk Factor Surveillance System (BRFSS) survey data and US Census data. We assigned ''hotspots'' around population centers with a range of various distances to wildfires in Alaska. Results: : We found that wildfires are associated with asthma prevalence, and the association is strongest within 25 miles of fires. Conclusions: : This study highlights the fact that proximity to wildfires has potential as a simple proxy for actual measured wildfire smoke, which has important implications for wildfire management agencies and for policy makers who must address health issues associated with wildfires, especially in rural areas.